2018
DOI: 10.15621/ijphy/2018/v5i3/173933
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Rated Outcome Measure Using Disease-specific Koos-PS Short Form Arabic Questionnaire in Knee Osteoarthritis

Abstract: Background: Several studies have evaluated the effects of knee osteoarthritis on general and specific activities of the population using various health-related questionnaires in their original/native form, but very few have reported in Saudi Arabian population using Arabic versions. The target of the study is to observe the degree of knee difficulties during pivoting, kneeling and squatting in bilateral knee osteoarthritis male patients using disease-specific Arabic Version Knee injury and osteoarthritis outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(33 reference statements)
0
1
0
Order By: Relevance
“… 3 , 5 , 6 A previous study on Saudi Arabian patients with knee injuries demonstrated that questionnaire translation is a beneficial method for obtaining accurate self-reported symptoms. 7 This type of research emphasizes the usefulness of symptom reporting when the questionnaire is administered in the patient's native language.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 5 , 6 A previous study on Saudi Arabian patients with knee injuries demonstrated that questionnaire translation is a beneficial method for obtaining accurate self-reported symptoms. 7 This type of research emphasizes the usefulness of symptom reporting when the questionnaire is administered in the patient's native language.…”
Section: Discussionmentioning
confidence: 99%